The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/1721727x1301100318
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lymphocyte Concentration in the Semen of Patients with Reduced Testicular Volume

Abstract: Low testicular volume (TV) is associated with a decreased testicular function. Several studies explored the conventional sperm parameters and the endocrine function in patients with low TV. No other parameters have been examined. On the basis of these premises, the aim of this study was to evaluate a non-conventional seminal parameter: seminal lymphocyte characterisation in men with low TV compared with that of subjects with normal TV. A further comparison was made between fertile men and infertile patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The systematic immunohistochemical analysis of testis biopsies from infertile patients with azoospermia indicated that immune cells were mainly infiltrated by CD3 + T cells, instead of CD20 + B cells and CD11c+ dendritic cells, regardless of the degree of inflammation [25]. In patients with a low testicular volume, a positive linear relationship was observed between CD45 lymphocytes infiltration and sperm parameters, such as the percentage of immature germ elements, phosphatidylserine externalization, early apoptosis, and abnormal morphology [26]. In a systematic re-examination of tissue samples obtained from chronic orchitis with infertility, the infiltration of T lymphocytes was recorded in as many as 56.3% of cases [27].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic immunohistochemical analysis of testis biopsies from infertile patients with azoospermia indicated that immune cells were mainly infiltrated by CD3 + T cells, instead of CD20 + B cells and CD11c+ dendritic cells, regardless of the degree of inflammation [25]. In patients with a low testicular volume, a positive linear relationship was observed between CD45 lymphocytes infiltration and sperm parameters, such as the percentage of immature germ elements, phosphatidylserine externalization, early apoptosis, and abnormal morphology [26]. In a systematic re-examination of tissue samples obtained from chronic orchitis with infertility, the infiltration of T lymphocytes was recorded in as many as 56.3% of cases [27].…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of CD45+ cells were observed in the chronically infected immunosuppressed pigs. CD45+ lymphocyte infiltration is directly associated with abnormal sperm morphology and early apoptosis of the sperm cells (51,52). Infiltration of CD45 in HEV infected mice testis has been attributed to the breakage of the BTB caused by HEV infection (15).…”
Section: Discussionmentioning
confidence: 99%